Pemberian Superfarm Rhizobium Dan Pupuk N Terhadap Pertumbuhan Dan Produksi Tanaman Kedelai (Glycine max L. Merill.) - Rika Agustina; Hamidah Hamidah; Akhmad Sopian (Agrifarm : Jurnal Ilmu Pertanian, 2016)
Giving Superfarm Rhizobium and N fertilizer on the Growth and Production of Soybean (Glycine max L. Merill.). The aim of research to determine the effect of Superfarm Rhizobium and N fertilizer on the growth and yield of soybean (Glycine max (L. Merill). The study was conducted over four months, from March to July 2015. The study in Dusun Desa Sumber Jaya Manunggal Jaya Rt. 09 District of Tenggarong Seberang Regency. this study used a draft split plot with factorial 3 x 4 consisting of three replications. the first factor is Superfarm Rhizobium which comprise three levels: ie s0 (without treatment), s1 (2 g / plant), s2 (4 g / plant). The second factor is the dose of N fertilizer consists of four levels ie N0 (without fertilizer) n1 (2.5G / plant) n2 (5g / plant) and n3 (7,5g / plant) . the results showed that treatment of Rhizobium Superfarm Award (S) had no significant effect on all parameters. While the provision of fertilizer N (N) significantly affected plant height parameter parameter 2, 4 and 6 weeks after planting. and at a dose of 7.5 g significantly the parameters of crop seed weight, seed weight per plot, the production results (Ton ha-1). The highest production was achieved by treatment s0n3 483.33 g / plot, equivalent to 2.69 Toh ha-1.